Postnatal administration of S-adenosylmethionine restores developmental AHR activation-induced deficits in CD8+ T-cell function during influenza A virus infection. (27th February 2023) - Post, Christina M; Myers, Jason R; Winans, Bethany; Lawrence, B Paige
Abstract: Developmental exposures can influence life-long health; yet, counteracting negative consequences is challenging due to poor understanding of cellular mechanisms. The aryl hydrocarbon receptor (AHR) binds many small molecules, including numerous pollutants. Developmental exposure to the signature environmental AHR ligand 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) significantly dampens adaptive immune responses to influenza A virus in adult offspring. CD8+ cytotoxic T lymphocytes (CTL) are crucial for successful infection resolution, which depends on the number generated and the complexity of their functionality. Prior studies showed developmental AHR activation significantly reduced the number of virus-specific CD8+ T cells, but impact on their functions is less clear. Other studies showed developmental exposure was associated with differences in DNA methylation in CD8+ T cells. Yet, empirical evidence that differences in DNA methylation are causally related to altered CD8+ T-cell function is lacking. The 2 objectives were to ascertain whether developmental AHR activation affects CTL function, and whether differences in methylation contribute to reduced CD8+ T-cell responses to infection. Developmental AHR triggering significantly reduced CTL polyfunctionality, and modified the transcriptional program of CD8+ T cells. S-adenosylmethionine, which increases DNA methylation, but not Zebularine, which diminishes DNA methylation, restored polyfunctionality and boosted the number of virus-specific CD8+ T cells. These findings suggest that diminished methylation, initiated by developmental exposure to an AHR-binding chemical, contributes to durable changes in antiviral CD8+ CTL functions later in life. Thus, deleterious consequence of development exposure to environmental chemicals is not permanently fixed, opening the door for interventional strategies to improve health.